KEDUDUKAN SURAT WASIAT TERHADAP HARTA WARISAN YANG BELUM DIBAGIKAN KEPADA AHLI WARIS - Sanjaya, Umar Haris (Jurnal Yuridis, 2018)
This research focused on the legal standing of testament toward inheritance property which devide yet. Testament recognized as a last will of person to be received by person who determined on it. Potentially, These will rise a dispute between testament receiver and the heir. It because of the heir would be bring it to the disputed if testament not desired. Thus, the testament would be not executed. This research using context of problems as how the legal standing of the testament toward inheritance property which devide yet and continue with is that testament should be execute absolutely toward inheritance property. Research result the testament has no absolutely legal standing to be execute toward inheritance property as long as rise the disputed. The dispute is related with the diclaimer from the heir toward testament substance. Thus, the testament is the last will of people do not perform well as the last will it because of the testament rejected probably. The rejection performed by court as well as the heir lawsuit.